2016
DOI: 10.1159/000442876
|View full text |Cite
|
Sign up to set email alerts
|

The Infrapatellar Adipose Body: A Histotopographic Study

Abstract: The infrapatellar fat pad (IFP) can be regarded as a peculiar form of fibro-adipose tissue localized close to the synovial membrane and articular cartilage. The aims of the present study were to analyze the microscopic anatomy of the IFP through histological and ultrastructural methods, comparing it with that of the subcutaneous tissue of the abdomen and of the knee. Ten specimens of IFP were sampled from bodies of the Donation Program of the University of Padua without a history of osteoarthritis. The IFP con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…According to the link between fibrosis, inflammation and mechanical load, we suggest that the peculiar phenotype of IAATs we describe here could depend on intrinsic properties of IAATs. A recent study comparing the histological characteristics of IFP from cadavers without knee OA to autologous knee SCAT and heterologous abdominal SCAT24 reported that IFP adipocytes were smaller than those from SCAT. However, their results on tissue fibrosis differ from ours.…”
Section: Discussionmentioning
confidence: 99%
“…According to the link between fibrosis, inflammation and mechanical load, we suggest that the peculiar phenotype of IAATs we describe here could depend on intrinsic properties of IAATs. A recent study comparing the histological characteristics of IFP from cadavers without knee OA to autologous knee SCAT and heterologous abdominal SCAT24 reported that IFP adipocytes were smaller than those from SCAT. However, their results on tissue fibrosis differ from ours.…”
Section: Discussionmentioning
confidence: 99%
“…). IFP is an extrasynovial but intracapsular adipose tissue attached to the intercondylar notch of femur by the IFP synovial plica (Macchi et al, ). Nonetheless, the exact role of IFP remains debated.…”
Section: Obesity and Related Comorbidities In Koamentioning
confidence: 99%
“…In fact, for its structural characteristics (lobular aspect of the adipose tissue, thickness of the septa with scarce elastic fibers Fig. ) (Macchi et al, ) IFP could act as a plastic portion aimed to absorption of pressure variations during knee articular activity (Macchi et al, ). However, recent evidence suggests that IFP might have not only a biomechanical ( Fontanella et al, ) but also a biochemical role in the pathogenesis of OA secreting inflammatory mediators like cytokines and adipokines (Clockaerts et al, ; Ioan‐Facsinay and Kloppenburg, ; Richter et al, ; Santangelo et al, ).…”
Section: Obesity and Related Comorbidities In Koamentioning
confidence: 99%
See 1 more Smart Citation
“…Using immunohistochemistry, the IFP showed free nerve fibres and nerves surrounded by thick multilaminated (three to six layers) connective tissue capsule. The free nerve fibres were recognizable within adipose lobules, whereas the corpuscles were recognizable along the interlobular septa, in the adipose lobules and close to the vessels (Macchi et al 2016). Moreover, the presence of type VIa free nerve endings is particularly important, as they may initiate afferent signals of pain, pressure and thermic variations to the central nervous system (Biedert & Kernen, 2001).…”
Section: Ifpmentioning
confidence: 99%